Mental health and other associated factors with fear of covid-19 among workers of oil and gas industry in Malaysia during covid-19 pandemic - Joseph Philip Kulip (2023)
The mankind mental health has been compromised during the existence of Coronavirus disease (Covid-19); an infectious disease caused by SARS-CoV-2 Virus which became pandemic on 11 March 2020 worldwide. There was limited availability of studies in this area affecting the mental health of the workers due to poor assessment. The objective was to assess the mental health in fear of Covid-19 among oil and gas workers. Through looking at the underlying psychological variables in time of Covid-19 pandemic, in the relationship of fear of Covid-19 with Sociodemographic and Occupational factors, DASS-21, and Brief-COPE. Data collection was done among the homogenous population of oil and gas industry workers by performing a cross-sectional study with an estimated sample size of 299. Research tools were Depression, Anxiety and Stress Scale 21 (DASS21), Brief COPE and fear of Covid-19 Scale (FCV-19S) as to assess the research variables. Questionnaire involves sociodemographic and occupational factor applied and data validation analysis done by using IBM SPSS Statistics 27 software. Result for the descriptive analyses of DASS-21 indicates a prevalence of 26.8% for depression, 33.4% for anxiety and 17.1% for stress among oil and gas workers. Using the Linear multiple regression, most result significantly show that all types of coping style (problem-oriented, emotional-oriented, and dysfunctional- oriented) were predictors of fear of COVID-19 with a result of β = -0.382, t = - 2.945, p = 0.003 in emotional-oriented coping, β = 0.430, t =3.017, p = 0.003 in problem-oriented coping and β = 0.460, t=4.586, p = < 0.001 for dysfunctional coping. Through these, it shows that dysfunctional coping style have the most significant results in fearing of Covid-19 study amongst workers in oil and gas industry in Sabah, Malaysia. In conclusion, there is a significant mental health issue in coping with the fear of Covid-19 that simultaneously came with depression, stress, and anxiety during pandemic of Covid-19 in the daily life of an oil and gas industry workers. It is through managing their coping style that the fear of COVID- 19 could be address by the upper management. Such as intensify the psychological intervention focusing the oil and gas personnel. Further research will be needed to enhance and improve the workers coping style to improve their mental health.